Dynamics Analysis and Experimental Research of Self-locking Descending Device of Mining Excavator - Bingbing Dong (Jixie chuandong)
The structure and working principle of the escapement type descending device for mining excavators are introduced. The reliability and dynamics performance of the descending device are theoretically analyzed. The three-dimensional structure of the descender is designed by CAD and UG software. The dynamics performance simulation is carried out with Adams software. The angular velocity and collision contact force of the main drive shaft are obtained respectively， and the stress analysis of the escape wheel is carried out. Finally， the performance of the test prototype is tested. The research results show that the mechanical structure of the escapement type descender does not show slipping during the falling process， and the strength and dynamics characteristics meet the requirements of use; the correctness of the simulation results is verified by experiments. The research results have a good guiding effect on the optimal design of the descending device.